The Papoose Board: Parents’ Perceptions and Attitudes of Its Usage in Their Child’s Dental Treatment - Mokhtar, Ilham Wan; Suhaimi, Aida Syazana Mohd; Ahmad, Mas Suryalis; Baharuddin, Izyan Hazwani; Andytan, Nur Iryani Izzaty (Journal of Dentistry Indonesia, 2019)
Parental perception and attitudes are important parameters in deciding the most suitable behavioral management technique for their children’s dental treatment. Objective: This study sought to evaluate parents’ perceptions, attitudes, and concern in using a papoose board (PB) on their child during dental treatment as a behavioral management technique in dentistry, as well as determine the sociodemographic factors associated with parents’ willingness to use the PB for their children’s dental care. Methods: One hundred parents from three locations with at least one healthy child aged between 4 and 7 years old were randomly identified. A self-made video (duration of 94 s) depicting the systematic placement of a PB on a child prior to dental treatment was viewed. Subsequently, each parent completed a validated 12-item questionnaire consisting of two domains: i) demographics and ii) acceptance given. A horizontal-visual analog scale was used to measure acceptance. Descriptive analysis, Pearson correlation coefficient, and simple logistic regression analysis were performed to generate the mean and standard deviation, frequency, percentage, and correlation. Results: Seventy-six parents completed the study. Approximately 63.2% of respondents felt that the PB is an effective technique to use, and 65.8% would permit its use during dental treatment for their children. However, 43.4% of respondents were worried about their child’s dental treatment. The age of the parents is a significant factor in their decision to use the PB. Conclusion: The PB appears to be well accepted by parents as a behavioral management technique in the condition that a proper explanation of its usage is given before its application.